Pre- and Post-operative determinants of transplantation-free survival after Fontan. The Australia and New Zealand experience. (August 2021) - Poh, Chin L.; Cordina, Rachael L.; Iyengar, Ajay J.; Zannino, Diana; Grigg, Leeanne E.; Wheaton, Gavin R.; Bullock, Andrew; Ayer, Julian; Alphonso, Nelson; Gentles, Thomas L.; Celermajer, David S.; d'Udekem, Yves
Abstract: Background: This review identifies the predictors of late mortality and heart transplantation that remain relevant in the contemporary population of patients with a Fontan circulation, focusing on the potential impact of post-Fontan morbidities on the late outlook of these patients. Methods and Results: A total of 1561 patients who had survived the Fontan operation in Australia or New Zealand from 1975 to 2018 were included in this review. Over a median duration of 11.4 years, there was a total of 117 deaths (7%) and 32 heart transplantations (2%). Freedom from death and heart transplantation at 10, 20 and 35 years post Fontan surgery were 94% (95% CI 93–95%), 87% (95 %CI 85–90%) and 66% (95 %CI 57–78%) respectively. Being male, having an atriopulmonary Fontan, pre-Fontan atrioventricular valve intervention, or prolonged pleural effusions post Fontan were predictive of late death or heart transplantation. However, time-dependent variables such as the development of atrial arrhythmia, protein/losing enteropathy or late ventricular dysfunction were stronger predictors of the same outcome. Patients who developed a time-dependent risk factor had a freedom from death and heart transplantation rate of 54% (95 %CI 43–66) at 15 years and 44% (95 %CI 33–57) at 25 years post Fontan. However, 95% (95 %CI 91–99) of patients without any of the identified risk factors were free from death or heart transplantation rate at 25 years post Fontan. Conclusion: In conclusion, the occurrence of post-operative complications such as PLE, arrhythmia and ventricular dysfunction will likely precede the late demise of these patients.